Structural Bioinformatics: exciting times in a rapidly evolving field - Cláudio M. Soares; Diana Lousa (FEBS Open Bio)
Structural Bioinformatics is a multidisciplinary field at the intersection of chemistry, physics, biology, and computer science. Its methods and approaches have been crucial in advancing scientific knowledge and breaking new ground. By extracting valuable insights from experimental data, generating predictions that accelerate research and reduce costs, and offering novel insights and testable hypotheses, Structural Bioinformatics plays a pivotal role in modern science. The field is undergoing transformative advancements, driven by developments in areas such as Artificial Intelligence. This special issue of FEBS Open Bio features five mini‐review articles by leading experts, providing an overview of some of the most recent advancements in Structural Bioinformatics.